Game Theory-Based Requirements Analysis in the i* Framework. (29th November 2017) - Subramanian, Chitra M; Krishna, Aneesh; Kaur, Arshinder
Abstract: In requirements engineering (RE), goal models have been employed to represent stakeholder objectives and to decide on suitable functional (goal) requirements, from among the system requirements. A large number of goal analysis procedure both qualitative and quantitative have been proposed for the selection of alternative requirements and goal achievement. All of these procedures perform goal analysis by considering the non-functional (softgoals) requirements with objective function of same nature, such as the maximising nature. However, there are real-time situations, where stakeholder's requirements have opposing objectives/requirements (one to be maximized and other to be minimized). Hence, there is a need for a goal analysis procedure, which can select an alternative design option in situations where there is a goal model with goals of opposing objective functions. In this paper, the game theory (GT)-based approach has been proposed to perform the analysis of goals with opposing objective functions. A tool for the GT-based goal analysis has been developed in Java, integrated with the IBM Cplex optimization tool and evaluated with the adapted goal models from the existing RE literature. The results of this evaluation indicate that the proposed approach assists in the selection of alternatives in real-life situations where there are goals with opposing objective functions.